Visualisasi Konstruk Abstrak: Analisis Kualitatif Persepsi Siswa Terhadap Penggunaan Canva Dalam Memahami Determinan Matriks - Rizka Maulidatun Nadifah; Nuryami Nuryami (FKIP UNSULTRA, 2026)
This study aims to analyze students’ perceptions of the use of Canva in constructing their understanding of matrix determinant concepts. This research employed a qualitative approach with an exploratory descriptive method. The participants consisted of 20 tenth-grade students at MA Progresif Ummul Quro selected through purposive sampling. Data were collected through semi-structured interviews, participatory observations, documentation, and questionnaires. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings revealed three main themes. First, Canva functioned as visual scaffolding that helped students understand abstract matrix determinant concepts through the use of colors, directional arrows, infographics, and structured visual representations. Second, Canva facilitated students’ transformation from procedural understanding toward conceptual understanding by enabling them to comprehend relationships among matrix elements and the meaning behind determinant formulas. Third, Canva positively influenced students’ affective experiences by increasing learning motivation, attention, confidence, and reducing mathematics anxiety. These findings indicate that Canva is not merely a presentation tool but also serves as a cognitive instrument that supports students in constructing mathematical knowledge. The study highlights the importance of integrating visual technology in mathematics learning to strengthen the connection between visual representation, mathematical symbols, and conceptual meaning. Therefore, Canva can be considered an effective digital learning medium for supporting meaningful mathematics learning in the 21st century.